2019
DOI: 10.1590/1807-1929/agriambi.v23n5p383-390
|View full text |Cite
|
Sign up to set email alerts
|

Correlations chart: Tool to analyse the dynamics of water quality parameters

Abstract: The search for statistical techniques and forms of graphical representation that can explain the most relevant correlations among limnological variables can help interpret phenomena in a body of water. The objective of the article was to propose a graphical representation of the correlations among limnological variables applied in the contributing basin of the Dr. João Penido reservoir, in Juiz de Fora, Minas Gerais state, Brazil. Six sections were monitored monthly from May 2012 to April 2014, analysing 15 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Regarding the results, they demonstrated that the class Forest brought a significant increase in DO and a significant decrease in TN, TP and TS. The pasture caused a significant increase in coliforms, TS and TP, being possible to notice, on the other hand, a decrease in DO, corroborating the results found by Rocha et al (2019a) in work carried out in that same area. The class Urbanization caused a significant increase in DO, coliforms, turbidity, conductivity and a significant decrease in TN.…”
Section: Kendall's Tau Correlating Land Use and Land Cover In The Cbjsupporting
confidence: 88%
See 3 more Smart Citations
“…Regarding the results, they demonstrated that the class Forest brought a significant increase in DO and a significant decrease in TN, TP and TS. The pasture caused a significant increase in coliforms, TS and TP, being possible to notice, on the other hand, a decrease in DO, corroborating the results found by Rocha et al (2019a) in work carried out in that same area. The class Urbanization caused a significant increase in DO, coliforms, turbidity, conductivity and a significant decrease in TN.…”
Section: Kendall's Tau Correlating Land Use and Land Cover In The Cbjsupporting
confidence: 88%
“…Vanzela et al (2010) also found a positive correlation between DO and pasture. The positive correlation with the nutrients TN (tau = 0.32) and TP (tau = 0.23) can also point to the effect of the transport of nutrients from these activities to bodies of water (Rocha et al, 2019a). Similar results with the nutrients TN and TP were observed by Buck et al (2004).…”
Section: Kendall's Tau Correlating Land Use and Land Cover In The Cbjsupporting
confidence: 67%
See 2 more Smart Citations
“…This ultimately helps in decision-making to monitor the water quality. Although a highly positive or negative (i.e., close to + 1 or − 1) value of r typically indicates a strong correlation, it is essential to assess the statistical significance or confidence of the correlation (Helena et al 2000;Rocha et al 2019). This can be achieved by the p value test.…”
Section: Correlationmentioning
confidence: 99%